P358 Keeping it simple: How a streamlined referrals process reduces the time taken to initiate biologic therapy. (21st January 2022) - Granger, E; Heyes, E; Cahoon, E; Riley, G; Kwok, J; Shuttleworth, E
Abstract: Background: The process of commencing IBD patients on biologic therapy is logistically complex. Most biologic therapy is administered via a subcutaneous or intravenous route, so in addition to a negative pre-biologic screen, patients must be educated on subcutaneous self-administration or booked into an infusion's clinic. A delay of over, 40 days in starting biologic therapy results in statistically worse self reported GI symptoms and endoscopic appearances at one year 1 . Therefore, reducing the time between the decision to initiate biologic treatment and the administration of the first dose is a key factor in improving outcomes. Methods: A retrospective review of clinic letters, appointment dates and email exchanges was performed for all IBD patients commenced on outpatient biologic therapy (Adalimumab, Infliximab, Vedolizumab, Ustekinumab, Golimumab and Tofacitinib) by the Gastroenterology team at Lancashire Teaching Hospitals NHS Trust between February, 2019 and September 2021. The length of time between the decision to initiate biologic therapy and the administration of the first dose was recorded in days. For cases where this time period was greater than, 28 days, the reason for the delay was categorised into either patient factors; logistical; outstanding biologic screen; outstanding clinical question; homecare delay or no single factor. A tracking spreadsheet and generic referral email address were introduced in March, 2021 and the impact of these interventions was assessed via run chart. Results: The median time period from the decision to initiate biologic therapy to administration of the first dose was, 35 days at the start of the study period, with, 67% of patients waiting over, 28 days. Following the interventions in March, 2021, despite twice the number of patients, the median wait time was reduced to, 20 days with only, 23% of patients waiting over, 28 days. Outstanding biologic screens and logistical factors such as delays in letter typing were the most common reasons for delays. Only, 17% of cases where communication was via email had a wait time of over, 28 days, compared to, 75% of cases where communication was via letter. Conclusion: Simple adjustments such as a dedicated tracking spreadsheet and switching to email communication have a big impact on streamlining the process of initiating biologic therapy, almost halving the time taken from decision to initiate therapy to administration of the first dose. 1 System delays have real consequences: Impact of timing of biologic commencement on inflammatory bowel disease patient response A McCulloch, Journal of Crohn's and Colitis, Volume, 13, Issue Supplement_1, March, 2019, Page S176